Taxonomic study of the Japanese endemic genus Yukikoa M. Satô (Coleoptera, Cantharidae) with descriptions of two new species - Nakamura, Ryo; Kubota, Kôhei (Zootaxa, 2023)
Two new species of the genus Yukikoa M. Satô, 1976 are described from Honshu, Japan: Y. mashimai sp. nov. from Niigata Prefecture and Y. nishimotoi sp. nov. from Fukui Prefecture. A revised key to the described species of Yukikoa and a distribution map are provided.